2017
DOI: 10.1002/qua.25393
|View full text |Cite
|
Sign up to set email alerts
|

Darmstadtium, roentgenium, and copernicium form strong bonds with cyanide

Abstract: We report the structures and properties of the cyanide complexes of three superheavy elements (darmstadtium, roentgenium, and copernicium) studied using two-and four-component relativistic methodologies. The electronic and structural properties of these complexes are compared to the corresponding complexes of platinum, gold, and mercury. The results indicate that these superheavy elements form strong bonds with cyanide. Moreover, the calculated absorption spectra of these superheavy-element cyanides show simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…A qualitative bonding analysis by Pyykkö et al, based on on the inspection of the molecular orbitals and in consideration of the short M–C bond distance (just few pm longer than those predicted for triple-bond covalent radii), suggested a multiple character of the Au–C bond. A similar conclusion has been drawn by Ruud et al in the case of AuCN. In photoelectron imaging experiments, Fan et al found that the electron affinities of CuCN and AgCN are larger than those of the metal atoms, while that for AuCN is smaller.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…A qualitative bonding analysis by Pyykkö et al, based on on the inspection of the molecular orbitals and in consideration of the short M–C bond distance (just few pm longer than those predicted for triple-bond covalent radii), suggested a multiple character of the Au–C bond. A similar conclusion has been drawn by Ruud et al in the case of AuCN. In photoelectron imaging experiments, Fan et al found that the electron affinities of CuCN and AgCN are larger than those of the metal atoms, while that for AuCN is smaller.…”
Section: Introductionsupporting
confidence: 89%
“…Photoelectron experiments on Au­(CN) 2 – , by comparison with its lighter congeners, Ag­(CN) 2 – and Cu­(CN) 2 – , hint at a significant covalent character of the Au–C bond. , The atomic-like transitions in Cu­(CN) 2 – are indeed consistent with a more ionic bond nature, whereas the bond in Ag­(CN) 2 – is expected to be of intermediate character. The authors point out that the high stability of Au­(CN) 2 – is consistent with the covalent character of the bond and surmise that s–d hybridization enhances gold ability to form multiple bonds, which would explain the short Au–C bond distance in this system. , A number of high-precision calculations already exist for the cyanides of noble metals (see refs and and references therein). Frenking et al investigated the metal–C bonds in cyanides and isocyanides of coinage metals ([M­(CN) 2 – ], with M = Cu, Ag, and Au), analyzing the chemical bond in terms of a well-defined energy partition scheme.…”
Section: Introductionmentioning
confidence: 77%
“…These multiple features of the AuÀ C bond in AuCN have been suggested in previous works. [27,28] It is very striking to realize that the so-called defects in the N�CÀ AuÀ C�N sequences increase their range order while the "ordered" C�NÀ AuÀ C�N sequences lose order by the grinding process. To understand this point, as well as to explain the observed transformations of the high-resolution C1s spectrum, it is necessary to elucidate the probable origin of the N�CÀ AuÀ C�N defects.…”
Section: X-ray Photoelectron Spectroscopymentioning
confidence: 99%
“…Palladium is a rare element that is used in many applications such as catalytic converters and fuel cell technologies. The valence ground state electron configuration of atomic palladium is closed-shell 4d 10 5s 0 , differing from all the other Group 10 members Ni (3d 8 5s 2 ), Pt (5d 9 6s 1 ), and Ds (6d 8 7s 2 ), which are open-shell [14,15]. In fact, Pd is the only known atom in its ground electronic state * paul.jerabek@gmail.com † p.a.schwerdtfeger@massey.ac.nz ‡ jnagle@bowdoin.edu not to have at least one electron in an outer-shell ns or np orbital [16].…”
Section: Introductionmentioning
confidence: 96%